Study on the effect of the treatment of Periplaneta americana L. extract Ento-B by Dinitrochlorobenzene combined with acetic acid induced UC in rats - Liu,Sheng-Shuai (2021)
ABSTRACT Purpose To study the Periplaneta americana L. extract Ento-B on the treatment of chronic ulcerative colitis induced by 2,4-dinitrochlorobenzene and acetic acid in rats and to explore its primary mechanism of action. Methods Using 2,4-dinitrochlorobenzene combined with acetic acid to induce chronic ulcerative colitis (chronic UC) in rats. The sulfasalazine (400 mg/kg) and Ento-B (200 mg/kg, 100 mg/kg,50 mg/kg) were given by intragastric administration and the effect was evaluated according to the disease activity index (DAI) score, colon mucosal injury index (CMDI) score, histopathological score (HS) and the serum levels of Interleukin-4(IL-4), Interleukin-10(IL-10), Tumor necrosis factor-α(TNF-α), Malondialdehyde(MDA), Superoxide dismutase(SOD) and Inducible nitric oxide synthase(iNOS.) Results Compared with the model group, all doses of Ento-B could reduce the score of CMDI (p < 0.05), HS(p < 0.05 or p < 0.01), significantly increased the expression of IL-4, IL-10, SOD (p < 0.01) and decreased the levels of TNF-α, MDA, iNOS in serum of UC rats, significantly improving the degree of colon lesionsin UC rats. Conclusions Ento-B may play an important role in the treatment of ulcerative colitis induced byUC rats. The mechanism may be related to the increased expression of IL-4, IL-10, SOD and reduced expression of TNF-α, MDA, iNOS.